IMPLEMENTATION OF THE MFEP METHOD IN DETERMINING THE PERFORMANCE OF VILLAGE GOVERNMENT APPARATUS BUHUNG SIBATU STONE - Arrizka Nazmi Sitorus; Hambali -; Sri Rezki Maulina Azmi (Jurnal Ipteks Terapan, 2022)
The village government is a government that channels the aspirations of the people from the community to the hamlet head and to the village hall led by a village head. A village head must be able to regulate and direct the apparatus to carry out quality government services. One of the methods used by the Village Head to improve quality services is to determine the performance of the government apparatus at the Village Hall Office. This method aims to determine the level of quality of the apparatus in the sub-district office. Apparatus assessment was also carried out by Bahung Sibatu Batu Village to determine the level of quality of the apparatus in the Village Hall Office. However, the assessment carried out now is still done manually on the assessment sheet and is still subjective, because there are no aspects of the assessment used in evaluating the performance of this apparatus. In assessing the performance of the apparatus of Bahung Sibatu Batu Village by evaluating which apparatus matches the criteria with the Village Head. The criteria for determining the performance of the apparatus include attendance, attitude, loyalty, responsibility and task completion. In addition to still using the conventional system, the closeness of the Village Head with employees often results in decisions that are different from what they should, this causes the results of the decisions to be inaccurate, so a decision support system is needed using the Multifactor Evaluation Process (MFEP) method.